Super-thick material layer sintering method
By controlling the fuel particle size, adding bentonite and improving the breathability of the material layer during the sintering process of the super-thick material layer, the sintering problem caused by the material layer resistance and self-weight is solved, and the effective increase of the material layer thickness and the reduction of the sintering cost is achieved.
Patent Information
- Application Number
- CN202510000418.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-25
AI Technical Summary
During the sintering process of super-thick material layer, the increase in material layer resistance and the self-weight of the material layer make it difficult to effectively carry out the sintering process, resulting in difficulty in effectively increasing the thickness of the material layer.
Through fuel particle size control, adding bentonite and atomizing water, using self-cleaning ventilation rods and unpowered surface drilling devices, the breathability and ball-forming strength of the material layer are improved, and the resistance of the material layer is reduced.
Under the thickness of the material layer of 950 to 1020 mm, the stability of the sintered mineral quality is ensured, the energy consumption of the sintering process is reduced, and the sintering cost is reduced.
Smart Images

Figure CN119876584A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metallurgy and relates to a super-thick material layer sintering method. Background Art
[0002] With the gradual deterioration of global iron ore resources and the increasingly stringent national environmental protection policies, the cost competitiveness of the steel industry continues to increase. How to improve the quality of sintered ore, reduce the energy consumption of the process, and then reduce the sintering cost has gradually become a hot spot and difficulty in the sintering industry research. Thick bed sintering technology, as an advanced sintering technology developed on the basis of calcium ferrite consolidation theory and automatic heat storage, has been applied to sintering sites since the 1980s and has been widely used and developed in recent years. Production practice has proved that thick bed sintering has the advantages of improving sintered ore quality and reducing process energy consumption.
[0003] In order to increase the thickness of the material layer and improve the economic and technical indicators of sintering, technicians have done a lot of exploration on the sintering method of ultra-thick material layer with a height of more than 900mm. However, as the thickness of the material layer increases, on the one hand, the resistance of the sintering process increases, and on the other hand, the weight of the material layer causes secondary damage to the sintering granulation, which makes it difficult to carry out the sintering process effectively. In other words, due to the limitation of technical level, the thickness of the material layer is difficult to effectively increase. Summary of the invention
[0004] The purpose of the present invention is to provide an ultra-thick layer sintering method, which effectively ensures the stability of the sintered ore quality under the condition of a layer thickness of 950-1020 mm, reduces the energy consumption of the sintering process, and thus reduces the sintering cost.
[0005] The technical solution of the present invention is: the present invention provides an ultra-thick material layer sintering method, characterized in that it includes the following steps: (1) fuel crushing: the fuel includes coal blocks and coke cubes, and the coal blocks and coke cubes are crushed and packaged separately, and transported to the sintering batching tank via a belt.
[0006] (2) Raw material batching: The raw materials are calculated in mass percentage and are discharged in the following order: mixed ore 60-65%, limestone 2.5-3.5%, dolomite 3.5-4.5%, coal powder 0.5-1.5%, coke powder 2.0-2.5%, quicklime 3.0-4.0%, blast furnace return ore 5-10%, sintering return ore 17-19%, dust removal ash 0.5-1.0%, bentonite 0-0.5%. The sum of the mass percentages of the above raw material components is 100%. Each material is quantitatively cut out by the raw material CFW belt scale and discharged to the aggregate belt in front of the primary mixer.
[0007] (3) Mixing and granulation: The mixed ore, quicklime, limestone, dolomite, coke powder, coal powder, blast furnace return ore, internal return ore, dust removal ash and bentonite are mixed and granulated in a primary mixer and a secondary mixer to obtain a sintering mixture; wherein, the primary mixer and the secondary mixer use atomizing nozzles to add water, and the moisture content of the mixture after adding water is controlled at 7.3-7.4%.
[0008] (4) Trolley material distribution: 4-8 rows of self-cleaning aeration rods are installed. After the material distribution operation is completed, the material layer thickness is 950-1020mm.
[0009] (5) Negative pressure ignition: When the material layer is fed into the ignition furnace, the pressure of the ignition furnace is controlled to be -5~0Pa, and the ignition temperature is 1100~1150℃, and negative pressure ignition is performed.
[0010] (6) Material surface drilling: During the sintering process of the material layer after ignition, move to the unpowered material surface drilling device to perform material surface drilling. The drilling depth is 150 to 250 mm and the drilling diameter is 30 to 60 mm.
[0011] (7) Sintering is completed.
[0012] Furthermore, the coal blocks and coke pieces are crushed by two-stage open-circuit crushing in a double-roll crusher and a four-roll crusher. The average particle size of the pulverized coal obtained after crushing is controlled at 1.8-2.0 mm, and the average particle size of the pulverized coke obtained after crushing is controlled at 1.4-1.6 mm. At the same time, the proportion of pulverized coal or pulverized coke with a particle size ≥ 3 mm is strictly controlled to be no more than 15%.
[0013] Furthermore, a particle size detection robot is installed in the middle of the first belt of the four-roll crusher, which can quickly detect the particle size of the fuel after crushing and upload the detection data to the central control. If it is found that the particle size deviates from the target range, the central control will remotely and automatically adjust the gap between the four rollers.
[0014] Furthermore, the amount of water added to the primary mixer is 20-40 t / h, and the amount of water added to the secondary mixer is 8-10 t / h.
[0015] Furthermore, baffle plates are added on both sides of the material distribution device of the trolley to realize the reloading of material on both sides of the trolley. The thickness of the material on both sides of the trolley is required to be 20-50mm higher than that in the middle. At the same time, pressure plates are installed on both sides of the trolley to compact the materials on both sides.
[0016] Furthermore, during the sintering process of the material layer, the flue negative pressure corresponding to the main exhaust fan is controlled to be 17.5-18.5 kPa.
[0017] The beneficial effects of the method of the present invention are as follows: the method of the present invention overcomes the problem of large material layer resistance during the sintering process of ultra-thick material layers, effectively ensuring the stability of the sintered ore quality under the condition of a material layer thickness of 950 to 1020 mm; and can reduce the energy consumption of the sintering process, thereby reducing the sintering cost.
[0018] The specific operation of reducing the material layer resistance in the method of the present invention is: (1) By controlling the particle size of the fuel after crushing, the permeability of the sintering process is ensured.
[0019] (2) By adding bentonite and using atomization and water addition during the mixing process, the granulation and balling effect of the mixture can be improved, the ball strength can be increased, and the secondary damage to the finished balls caused by the deadweight of the material layer can be weakened. At the same time, a self-cleaning ventilation rod can be used to effectively improve the air permeability of the original sintering material layer, providing strong support for the sintering of thick material layers.
[0020] (3) By adding material blocking and pressing devices on both sides of the trolley and applying non-powered material surface punching devices, harmful air leakage at the edges of the railings on both sides of the sintering trolley is weakened, and effective air extraction during the sintering process is improved. At the same time, appropriate coke particle size is matched to maintain good hot air permeability to ensure effective sintering of thick material layers.
[0021] (4) Punch holes on the material surface to improve the air permeability during the sintering process. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION
[0023] The present invention will be further described below in conjunction with the accompanying drawings. Example 1
[0024] like Figure 1 As shown, the present invention discloses a method for sintering an ultra-thick material layer, and the implementation steps are as follows.
[0025] Fuel crushing: Fuel crushing adopts closed-loop control. Considering the differences in ash, volatile matter and heat between coal and coke, coal and coke are required to be crushed separately, loaded into the tank separately, and cut out in a certain proportion. Mixing and mixing is strictly prohibited. Specifically, double-roll crusher and four-roll crusher are used to crush and pack the sintering fuel (coal blocks, coke cubes) separately. And the particle size of the fuel after crushing is controlled. The average particle size of the pulverized coal obtained after crushing is controlled at 1.9mm, and the average particle size of the pulverized coke obtained after crushing is controlled at 1.6mm. At the same time, the proportion of pulverized coal or pulverized coke with a particle size ≥3mm is strictly controlled to be no more than 15%.
[0026] Specifically, for the control of particle size, a particle size detection robot can be installed in the middle of the first belt of the four-roller unloading to realize the rapid detection of the particle size after the sintered fuel is crushed, and the detection data can be uploaded to the central control. If the particle size deviates from the target range, the central control can remotely and automatically adjust the gap between the four rollers.
[0027] Raw material batching: The raw materials are calculated by mass percentage and are discharged in the following order: 62% mixed ore, 3.0% limestone, 4.2% dolomite, 1.4% coal powder, 2.1% coke powder, 3.5% quicklime, 6% blast furnace return ore, 17.0% sintering return ore, 0.6% dust removal ash, and 0.2% bentonite. Each material is quantitatively cut out by the raw material CFW belt scale and discharged to the aggregate belt in front of the primary mixer.
[0028] A small proportion of bentonite is added to the ingredients of the present invention, which can enhance the granulation effect. Bentonite has good adsorption, adhesion, dispersibility and expansion. After adding bentonite, the proportion of particles ≤1 mm after granulation of the sintered mixture is reduced by 2% to 10% year-on-year, and the average particle size of the mixture particles is increased by 0.2 to 0.5 mm year-on-year. At the same time, the ball strength of the mixture is significantly improved, and the air permeability of the sintered original material layer is effectively improved.
[0029] (3) Mixing and granulation: Mix the ore, flux (quicklime, limestone, dolomite), fuel (coke powder, coal powder), blast furnace return ore, internal return ore, dust removal ash and bentonite through a primary mixer and a secondary mixer to obtain a sintering mixture; water is added in the primary mixer and the secondary mixer using an atomizing nozzle to ensure that water can be added evenly during the mixing process. The water addition rate of the primary mixer is 25t / h, and the water addition rate of the primary mixer is 8t / h. After adding water, the moisture content of the granulated mixture is controlled at 7.3%.
[0030] (4) Trolley material distribution: 6 rows of self-cleaning ventilation rods are installed to ensure good air permeability of the original material layer. Add baffle plates on both sides of the trolley material distribution device to realize the reloading of materials on both sides of the trolley. The thickness of the materials on both sides of the trolley is required to be 20 to 50 mm higher than that in the middle. At the same time, press plates are installed on both sides of the trolley to compact the materials on both sides.
[0031] Specifically, the number of aeration rods is set to 6 rows, and a vibration motor is installed on the base of the aeration rods to realize self-cleaning of accumulated materials on the aeration rods. The longitudinal height of the first row of aeration rods from the grate bars at the bottom of the trolley is 200-300mm, and the horizontal spacing between the two side rods and the trolley railing is 600mm, totaling 11. The longitudinal height of the second row of aeration rods is 120mm from the first row, and they are arranged crosswise with the first row. The horizontal spacing between the two side rods and the trolley railing is 410mm, totaling 12. The number and horizontal arrangement of aeration rods in the third and fifth rows are the same as those in the first row, and the number and horizontal arrangement of aeration rods in the fourth and sixth rows are the same as those in the second row. The longitudinal spacing between each row of aeration rods is 120mm, and the length of the aeration rods is based on the eleventh roller of the eleven-roller feeder. The aeration rod material is stainless steel wear-resistant rod with a diameter of 25-35mm. At the same time, the base of the aeration rod is evenly divided into 2 to 4 parts in the horizontal direction, and a vibration motor is installed on each base. An automatic control program is developed, and the central control sets the cleaning cycle to achieve periodic cleaning of the aeration rod. The application of this device improves the air permeability of the material layer and solves the problems of uneven distribution, accumulation and grooves caused by the accumulation of material on the aeration rod.
[0032] In addition, using the pressure plates installed on both sides of the trolley to compact the materials on both sides can increase the stacking density and thus reduce harmful air leakage on both sides.
[0033] (5) Negative pressure ignition: By adjusting the 1-5 bellows valve plates under the ignition furnace, the negative pressure in the sintering ignition furnace is controlled to -0.3 Pa, and the ignition temperature is 1130°C. Slightly negative pressure ignition is achieved to improve the air permeability of the sintering raw material layer.
[0034] (6) Material surface drilling: A non-powered material surface drilling device is installed at the No. 9 wind box position behind the sintering ignition and insulation furnace. The drilling depth is 200 mm and the drilling diameter is 50 mm. This reduces the material layer resistance of the surface sintered ore and improves the permeability of the material layer, creating favorable conditions for the subsequent thick material layer sintering.
[0035] (7) Sintering is completed.
[0036] The sintering machine used in the present invention has a length of 110m. The sintering machine is fed to the sintering machine trolley through a shuttle feeder, a mud roller, an eleven-roller mixing device, etc. at the machine head. The material is loosened by six rows of ventilation rods. The material thickness is 1010mm. The sintering is ignited and sintered by exhaust air through an igniter. The ignition temperature is 1130℃, the exhaust air negative pressure is 18.0kpa, and the sintering machine speed is set to 1.9m / min. By adopting the sintering method of the present invention, the comprehensive rate of sintered ore entering the furnace is increased from 70.9% to 73.0%, the energy consumption of the sintering process is reduced from 39.4kgce / t to 38.2kgce / t, the unit consumption of solid fuel is reduced from 46.9kg / t to 46.5kg / t, and the ignition gas consumption is reduced from 3.9m 3 / t reduced to 3.2m 3 / t. Example 2
[0037] The implementation steps of Example 2 are the same as those of Example 1, but the raw material ratios used are different. The raw material ratios in this example are as follows: each raw material is calculated by mass percentage and is discharged in the following order: 62.3% of mixed ore, 2.6% of limestone, 3.7% of dolomite, 1.3% of coal powder, 2.1% of coke powder, 3.3% of quicklime, 6.5% of blast furnace return ore, 17.1% of sintering return ore, 0.9% of dust removal ash, and 0.2% of bentonite. Each material is quantitatively cut out by the raw material CFW belt scale and discharged to the aggregate belt in front of the primary mixer.
[0038] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for sintering an ultra-thick material layer, characterized in that: The steps include: (1) Fuel crushing: The fuel includes coal blocks and coke cubes. The coal blocks and coke cubes are crushed and packaged separately and transported to the sintering batching tank via a belt conveyor; (2) Raw material batching: The raw materials are calculated by mass percentage and are discharged in the following order: mixed ore 60-65%, limestone 2.5-3.5%, dolomite 3.5-4.5%, coal powder 0.5-1.5%, coke powder 2.0-2.5%, quicklime 3.0-4.0%, blast furnace return ore 5-10%, sintering return ore 17-19%, dust removal ash 0.5-1.0%, bentonite 0-0.5%, and the sum of the mass percentages of the above raw material components is 100%; each material is quantitatively cut out by the raw material CFW belt scale and discharged to the aggregate belt in front of the primary mixer; (3) Mixing and granulation: Mix the ore, quicklime, limestone, dolomite, coke powder, coal powder, blast furnace return ore, internal return ore, dust removal ash and bentonite through a primary mixer and a secondary mixer to obtain a sintering mixture; the primary mixer and the secondary mixer use atomizing nozzles to add water, and the moisture content of the mixture after adding water is controlled at 7.3-7.4%; (4) Trolley material distribution: 4-8 rows of self-cleaning aeration rods are set. After the material distribution operation is completed, the material layer thickness is 950-1020mm; (5) Negative pressure ignition: When the material layer is fed into the ignition furnace, the pressure of the ignition furnace is controlled to be -5~0Pa, and the ignition temperature is 1100~1150℃, and negative pressure ignition is performed; (6) Material surface punching: During the sintering process of the material layer after ignition, move to the unpowered material surface punching device to punch holes on the material surface. The punching depth is 150-250 mm and the punching diameter is 30-60 mm. (7) Sintering is completed.
2. The ultra-thick material layer sintering method according to claim 1, characterized in that: The coal blocks and coke pieces are crushed by two-stage open-circuit crushing in a double-roll crusher and a four-roll crusher. The average particle size of the pulverized coal obtained after crushing is controlled at 1.8-2.0 mm, and the average particle size of the pulverized coke obtained after crushing is controlled at 1.4-1.6 mm. At the same time, the proportion of pulverized coal or pulverized coke with a particle size ≥ 3 mm is strictly controlled to be no more than 15%.
3. The ultra-thick material layer sintering method according to claim 2, characterized in that: A particle size detection robot is installed in the middle of the first belt of the four-roll crusher. It can quickly detect the particle size of the fuel after crushing and upload the detection data to the central control. If it is found that the particle size deviates from the target range, the central control will remotely and automatically adjust the gap between the four rollers.
4. The ultra-thick material layer sintering method according to claim 1, characterized in that: The amount of water added by the primary mixer is 20-40 t / h, and the amount of water added by the secondary mixer is 8-10 t / h.
5. The ultra-thick material layer sintering method according to claim 1, characterized in that: Add material blocking plates on both sides of the material distributing device of the trolley to realize the reloading of material on both sides of the trolley. The material thickness on both sides of the trolley is required to be 20-50mm higher than that in the middle. At the same time, press plates are installed on both sides of the trolley to compact the materials on both sides.
6. The ultra-thick material layer sintering method according to any one of claims 1 to 5, characterized in that: During the sintering process of the material layer, the flue negative pressure corresponding to the main exhaust fan is controlled at 17.5~18.5kpa.